IMPLEMENTASI MEDIA AUGMENTED REALITY (AR) DALAM PEMBELAJARAN IPAS KELAS 4 DI SD KADIPIRO SURAKARTA TAHUN AJARAN 2024/2025 - Marcellya Wahyu Ayudia; Hera Heru Sri Suryanti; Muhammad Faruq Hanafi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the implementation of Augmented Reality (AR) media in science and social studies (IPAS) learning using the Assemblr Edu application for fourth-grade students at SD Kadipiro Surakarta in the 2024/2025 academic year. The use of technology-based learning media is expected to enhance students’ interest and understanding of abstract learning materials. This study employed a descriptive qualitative method with a case study design. The research subjects consisted of the fourth-grade teacher and students. Data were collected through observation, interviews, and documentation. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results indicate that the implementation of Augmented Reality (AR) media improves students’ learning interest, facilitates their understanding of abstract concepts, and creates a more interactive and engaging learning environment. It also assists teachers in delivering material more effectively. Therefore, Augmented Reality(AR) can serve as an alternative instructional media to support IPAS learning in elementary schools.